Pengaruh Variasi Lilitan Pipa Kapiler pada Line Suction terhadap Laju Pendinginan dan Capaian Suhu Optimal Ruangan Prototype Trainer Lemari Pendingin - Darmawan, Gede; Wiratmaja, I Gede; Elisa, Edi (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to find the effect of variations in the capillary tube winding on the suction line on achieving optimal temperature and room cooling rate. This study uses three variations: the capillary tube without being wrapped around the suction line, the capillary tube wrapped in half on the suction line, and the capillary tube fully wound on the suction line. Specifically, the purpose of this study was to determine the effect of variations in the capillary tube wrapped around the suction line, which led to efforts to maintain the performance of the refrigerator trainer prototype. The method used in this study uses an experimental method where the data collection process is carried out through observation and documentation. The data analysis technique used in this study uses quantitative descriptive research techniques where the research data will be tabulated and displayed in the form of tables and graphs, and data analysis is carried out to find out how much influence the achievement of the optimal room temperature and the cooling rate of the prototype trainer refrigerator room itself. From the research that has been carried out, it is obtained that the highest optimal room temperature achievement occurs in the variation of the capillary tube fully wound on the suction line, where there is an increase in the optimal room temperature achievement of 16.17% when compared to the room cooling rate using standard variations or without being wrapped. And the result in the form of the highest room cooling rate is the variation of the capillary pipe fully wound on the suction line.